REPORT ON THE IMPACT DANCERS OF INJURIES IN CLASSICAL BALLET ACADEMIES IN THE CITY OF FORTALEZA / CE (Fiep Bulletin - online, 2014)
The Classical Ballet is an art that requires a lot of physical skills and athletic training, expressing itself by elaborate movements that are performed following a pace that is predetermined by the music. The objective of this study was to investigate the basis of statements of the dancers themselves incidence of injuries in classical ballet academies in the city of Fortaleza / CE. To achieve the objective of the study was conducted field research with descriptive exploratory quantitative approach, based on bibliographical studies. Obtaining the results were taken from a semi-structured questionnaire containing 06 open questions and 13 closed questions, performed with 50 dancers (a) of both sexes, aged 13-24 years, with over five years of practice dance. The results showed that 78% of dancers train on Saturdays and 10% also train on Sundays. We found that 60% of the dancers had already lesion somewhere in the body, 58% have 4 hours of daily lessons / test and 38% feel constant pain during and / or after school / testing. From these results we conclude that there is a high prevalence of injury among practitioners of classical ballet. And it is suggested greater attention to the professional activity of the dancers, as they have workload similar to athletes coordination procedures complex.
Keywords: classical ballet; injuries; training.